DNA driven self-assembly of micron-sized rods using DNA-grafted bacteriophage fd virions1. Issue 12 (28th March 2015) - Unwin, R. R.; Cabanas, R. A.; Yanagishima, T.; Blower, T. R.; Takahashi, H.; Salmond, G. P. C.; Edwardson, J. M.; Fraden, S.; Eiser, E.
<x xml:space="preserve">Abstract</x> We observe aggregation of high aspect ratio, semi-flexible viral rods functionalized with complementary, single-stranded DNA oligomers.